India’s ongoing rooftop solar journey 2017–2022 - Mukherjee, M (Oxford Institute for Energy Studies, 2022)
India is often taken as a microcosm for much of the developing world because people living in many different circumstances in the country are representative of what is found in large parts of the developing world. This is particularly relevant for clean technologies that are consumer-led and therefore require an upfront financial contribution from consumers, such as rooftop solar which is the subject of this paper.